Body mass index, C-reactive protein, and pancreatic cancer: A Mendelian randomization analysis to investigate causal pathways - Li, Zhenqi; Jin, Liquan; Xia, Lu; Li, Xiangzhi; Guan, Yunfei; He, Hongyang (Frontiers in Oncology, 2023)
Aim To explore whether C-reactive protein (CRP) mediates the risk of body mass index (BMI) in pancreatic cancer (PC) and calculate the mediate proportion of CRP in this possible mechanism. Methods Based on two-sample Mendelian randomization (TSMR), a two-step Mendelian randomization (TM) model was conducted to determine whether CRP was a mediator of the causal relationship between BMI and PC. The multivariable Mendelian randomization (MVMR) study was designed for mediating analysis and to calculate the mediating proportion mediated by CRP. Results BMI has a positive causal relationship with PC (n = 393 SNPs, OR = 1.484, 95% CI: 1.021–2.157, p< 0.05). BMI has a positive causal relationship with CRP (n = 179 SNPs, OR = 1.393, 95% CI: 1.320–1.469, p< 0.05). CRP has a positive causal relationship with PC (n = 54 SNPs, OR = 1.348, 95% CI: 1.004–1.809, p< 0.05). After adjusting CRP, BMI has no causal relationship with PC (n = 334 SNPs, OR = 1.341, 95% CI: 0.884–2.037, p< 0.05). After adjusting BMI, there was still a positive causal relationship between CRP and PC (n = 334 SNPs, OR = 1.441, 95% CI: 1.064–1.950, p< 0.05). The mediating effect of CRP was 29%. Conclusions In clinical practice, while actively advocating for weight loss among obese patients, we should focus on chronic inflammation levels in obese patients as well. In addition, anti-inflammatory dietary patterns and appropriate physical activity are important in preventing PC.